Persistent HIV transcription and variable antiretroviral drug penetration in lymph nodes during plasma viral suppression. (1st June 2022) - Fletcher, Courtney V.; Kroon, Eugène; Schacker, Timothy; Pinyakorn, Suteeraporn; Chomont, Nicolas; Chottanapund, Suthat; Prueksakaew, Peeriya; Benjapornpong, Khunthalee; Buranapraditkun, Supranee; Phanuphak, Nittaya; Ananworanich, Jintanat; Vasan, Sandhya; et al.
Abstract : Objective: The ability of antiretroviral drugs to penetrate and suppress viral replication in tissue reservoir sites is critical for HIV remission. We evaluated antiretroviral concentrations in lymph nodes and their impact on HIV transcription. Methods: Participants of the RV254/SEARCH010 Acute HIV Infection Cohort in Thailand were enrolled. Group 1 (n   =  6) initiated and continued antiretrovirals with two nucleoside reverse transcriptase inhibitors (NRTIs), dolutegravir (DTG) and mar- aviroc (MVC). Group 2 (n = 12) initiated antiretrovirals with two NRTIs as well as efavirenz and were switched to two NRTIs as well as DTG. Antiretroviral concentrations were measured by mass spectroscopy. HIV RNA+ and DNA+ cells were measured by in-situ hybridization. Results: All participants were MSM. At lymph node biopsy, all had plasma HIV RNA less than 20 copies/ml. Group 2 had longer durations of antiretroviral and DTG use (medians of 135 and 63 weeks, respectively) compared with Group 1 (median 44 weeks for both). TFV-DP, 3TC-TP, DTG and MVC were quantifiable in all lymph node samples from participants receiving those drugs versus carbovir-triphosphate (CBV-TP) in four out of 14. Median ratios of lymph node to peripheral blood concentrations were DTG, 0.014; MVC, 6.9; CBV-TP, 0.38; 3TC-TP, 0.32; and TFV-DP, 3.78. Median inhibitory quotients [ratios of lymph node concentrations to in-vitro inhibitory levels (IC50-or-90 )] were DTG, 0.8; MVC, 38.8; CBV-TP, 0.5; 3TC- TP, 4.1; and TFV-DP, 1.8. Ongoing viral transcription was detected in lymph node of all participants. Median lymph node RNA+ cells were 71 350 versus 99 750 cells/g for Groups 1 and 2, respectively (P = 0.111). Conclusion: MVC has enhanced lymph node penetration and thereby may contribute to more complete viral suppression in the lymph node.